Anti-corrosion high-performance stainless steel pipe and preparation method thereof

CN122898797APending Publication Date: 2026-10-13JIANGYIN SOUTH STAINLESS STEEL PIPES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611110496.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-24
Publication Date
2026-10-13

AI Technical Summary

Technical Problem

但普通的不锈钢管在应用于高温、潮湿、易腐蚀的恶劣环境中时,其耐腐蚀性能存在明显不足,难以满足使用需求

Benefits of technology

本发明的不锈钢管本体中,通过各元素的协同复配,使不锈钢管本体兼具优异的力学强度和良好的防腐性能;

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application discloses an anti-corrosion high-performance stainless steel pipe and a preparation method thereof. The anti-corrosion high-performance stainless steel pipe comprises a stainless steel pipe body and an anti-corrosion coating arranged on the surface of the stainless steel pipe body. The raw material components of the stainless steel pipe body comprise the following components in percentage by mass: C: 0.025-0.036%, Cr: 17.5-20.8%, Mn: 1.4-2.2%, Ni: 8.0-11.5%, Mo: 0.46-0.92%, Si: 0.35-0.52%, N: 0.10-0.16%, Nb: 0.06-0.11%, and the rest is Fe. In the stainless steel pipe body, the elements are synergistically compounded, so that the stainless steel pipe body has excellent mechanical strength and good corrosion resistance. The anti-corrosion coating formed on the surface of the stainless steel pipe body can further improve the corrosion resistance, heat resistance and weather resistance, and good protection is realized on the stainless steel pipe body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of stainless steel corrosion protection technology, and in particular to a high-performance corrosion-resistant stainless steel pipe and its preparation method. Background Technology

[0002] Pipe fittings are a collective term for components in a piping system that serve functions such as connection, control, direction change, flow diversion, sealing, and support. Steel pipe fittings have excellent strength and heat resistance and are widely used. However, ordinary stainless steel pipes have significantly insufficient corrosion resistance when used in harsh environments such as high temperature, humidity, and easy corrosion, making it difficult to meet the application requirements.

[0003] Patent CN113430509B discloses an anti-corrosion treatment process for stainless steel pipe fittings. By optimizing the passivation process, the anti-corrosion performance of stainless steel pipes can be improved, but there is still considerable room for improvement in the effect.

[0004] Therefore, it is now necessary to improve existing technologies to provide more reliable solutions. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a corrosion-resistant high-performance stainless steel pipe and its preparation method, addressing the shortcomings of the prior art.

[0006] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: a corrosion-resistant high-performance stainless steel pipe, comprising a stainless steel pipe body and an anti-corrosion coating disposed on the surface of the stainless steel pipe body, wherein the raw material components of the stainless steel pipe body include, by mass percentage: C: 0.025-0.036%, Cr: 17.5-20.8%, Mn: 1.4-2.2%, Ni: 8.0-11.5%, Mo: 0.46-0.92%, Si: 0.35-0.52%, N: 0.10-0.16%, Nb: 0.06-0.11%, balance Fe.

[0007] Preferably, the anti-corrosion coating is obtained by applying an anti-corrosion paint and then curing it, and the anti-corrosion paint comprises the following components by weight: The ingredients are: 100 parts waterborne polyurethane resin, 15-25 parts glass flake-graphene oxide composite filler, 34-55 parts curing agent, 0.4-1.6 parts dispersant, 0.5-2 parts defoamer, 0.2-0.8 parts thickener, 0.5-2 parts leveling agent, 1-4 parts film-forming aid, and 20-40 parts deionized water.

[0008] Preferably, the glass flake-graphene oxide composite filler is prepared by the following method: S1. Modify the glass flakes with a silane coupling agent to obtain activated glass flakes: S2. Fe2O3-GO hybrid is deposited on activated glass flakes to obtain the complex intermediate; S3. Coating the surface of the composite intermediate with polyaniline to obtain the glass flake-graphene oxide composite filler.

[0009] Preferably, the silane coupling agent used in step S1 is a mixture of KH-550 and KH-560 in a mass ratio of 1:0.2~0.8.

[0010] Preferably, step S1 specifically involves: adding glass flakes to deionized water, adjusting the pH to 4-5 with hydrochloric acid, ultrasonically dispersing the flakes, adding silane coupling agents KH-550 and KH-560, stirring the mixture under heating, filtering the mixture after the reaction is complete, washing and drying the solid to obtain activated glass flakes.

[0011] Preferably, step S2 specifically includes: S2-1. Take activated glass flakes and disperse them in deionized water to obtain a glass flake suspension; take FeCl3·6H2O and add it to 40mL of deionized water, adjust the pH to 1-2, and obtain a ferric chloride solution; take graphene oxide powder and disperse it in deionized water to obtain a GO dispersion. S2-2. While stirring, ferric chloride solution and GO dispersion are simultaneously added dropwise to the glass flake suspension. Stir, adjust the pH to 8.5-10, and stir to react. S2-3. After the reaction is complete, the mixture is aged, filtered, washed, dried, calcined, cooled, and ground to obtain the complex intermediate.

[0012] Preferably, step S3 specifically involves: adding the composite intermediate and sodium dodecylbenzenesulfonate to deionized water, ultrasonically dispersing them, adding aniline, stirring, and simultaneously adding hydrochloric acid solution and ammonium persulfate aqueous solution, stirring the reaction, filtering after the reaction is complete, washing, drying, and grinding the solid to obtain the glass flake-graphene oxide composite filler.

[0013] Preferably, the glass flake-graphene oxide composite filler is prepared by the following method: S1. Preparation of activated glass flakes: Add 5-20g of glass flakes to 200-800mL of deionized water, adjust the pH to 4-5 with hydrochloric acid, and sonicate for 0.5-2h. Then add 0.5-2g of silane coupling agent KH-550 and 0.25-1g of silane coupling agent KH-560, stir and react at 50-75℃ for 1.5-6h, centrifuge and filter, wash the solid with ethanol, and dry to obtain activated glass flakes. S2. Deposition of Fe2O3-GO hybrid on activated glass flakes: S2-1. Take 5-20g of activated glass flakes and add them to 100-400mL of deionized water. Disperse by ultrasonication for 20-80min to obtain a glass flake suspension. Take 2.7-10.8g of FeCl3·6H2O and add it to 20-80mL of deionized water. Adjust the pH to 2 with hydrochloric acid and stir for 5-20min to obtain a ferric chloride solution. Take 0.2-0.8g of graphene oxide powder and add it to 30-120mL of deionized water. Disperse by ultrasonication for 0.5-2h to obtain a GO dispersion. S2-2. While stirring, ferric chloride solution and GO dispersion are simultaneously added dropwise to the glass flake suspension over a period of 15-60 min. After the addition is complete, stir for 0.5-2 h. Then, adjust the pH to 8.5-10 with 0.05-0.2 mol / L NaOH solution and stir the reaction for 1-4 h. S2-3. After the reaction is complete, age for 2-8 hours, filter, wash the solid with deionized water, dry at 90-110℃ for 2-8 hours, then calcine at 450-550℃ for 1.5-4 hours, cool to room temperature, grind, and obtain the complex intermediate. S3. Coating the surface of the composite intermediate with polyaniline: Add 2.5-10g of the complex intermediate and 0.15-0.6g of sodium dodecylbenzenesulfonate to 100-400mL of deionized water and sonicate for 15-60min. Then add 8-32g of aniline and stir for 10-40min. Simultaneously add 10-50mL of 0.1-0.5mol / L hydrochloric acid solution and 10-50mL of ammonium persulfate aqueous solution containing 10-30g of ammonium persulfate. Stir and react at 0-10℃ for 12-48h. Centrifuge and filter. Wash the solid with deionized water, vacuum dry, and grind to obtain the glass flake-graphene oxide composite filler.

[0014] Preferably, the dispersant is BYK-190, the defoamer is BYK-024, the thickener is RM-2020, the leveling agent is BYK-348, and the film-forming aid is propylene glycol methyl ether acetate.

[0015] The present invention also provides a manufacturing process for the corrosion-resistant high-performance stainless steel pipe as described above, comprising the following steps: Step 1: Weigh the raw materials for the stainless steel pipe body according to the following mass percentages: C: 0.025-0.036%, Cr: 17.5-20.8%, Mn: 1.4-2.2%, Ni: 8.0-11.5%, Mo: 0.46-0.92%, Si: 0.35-0.52%, N: 0.10-0.16%, Nb: 0.06-0.11%, balance Fe; Step 2: Mix and melt the raw materials of the stainless steel pipe body, cast the molten steel to obtain a steel plate, and then roll, weld, hot roll, and solution treat the steel plate to obtain the stainless steel pipe body. Step 3: Spray anti-corrosion coating on the inner and outer surfaces of the stainless steel pipe body, dry and cure to form an anti-corrosion coating, and obtain the anti-corrosion high-performance stainless steel pipe.

[0016] Invention Mechanism 1. The formula for the stainless steel pipe body of the present invention includes: Chromium (Cr) forms a dense and stable Cr2O3 passivation film on the pipe surface, blocking the penetration of corrosive media and improving resistance to atmospheric, acid, alkali, and salt spray corrosion, while also enhancing the pipe's oxidation resistance. Nickel (Ni) stabilizes the austenitic structure, eliminates steel brittleness, improves the pipe's toughness, fatigue resistance, and hot and cold working properties, avoids pipe forming cracking problems, and synergistically enhances electrochemical corrosion resistance with chromium. Nitrogen (N) improves the pipe's tensile strength and yield strength without reducing toughness through the formation of intermetallic compounds, while also improving grain boundary corrosion resistance and inhibiting intergranular corrosion. Niobium (Nb) refines grains, improves the pipe's high-temperature strength and structural stability, and enhances corrosion resistance. Silicon (Si) refines the as-cast structure, improving the pipe's forming uniformity and structural density. The synergistic combination of these elements gives the stainless steel pipe both excellent mechanical strength and good corrosion resistance.

[0017] 2. The anti-corrosion coating of the present invention uses water-based polyurethane resin as the main resin. By compounding and adding glass flake-graphene oxide composite filler, the anti-corrosion barrier, heat resistance and weather resistance of the coating can be significantly improved, and good protection of the stainless steel pipe body can be achieved.

[0018] The preparation process of the glass flake-graphene oxide composite filler is as follows: First, a large number of hydroxyl active sites are generated on the surface of glass flakes by etching with dilute acid. Then, the glass flakes are activated and modified by using a combination of silane coupling agents KH-550 and KH-560, introducing amino and epoxy active groups. The amino groups have the ability to react with Fe. 3+ Through coordination, epoxy active groups can form chemical bonds with subsequent polyaniline molecules, thereby enhancing interfacial bonding. Subsequently, a hybrid of Fe2O3 and graphene oxide (GO) is deposited on glass flakes. Simultaneous co-deposition forms a nano-interwoven hybrid layer. GO sheets intersect and anchor Fe2O3 grains, inhibiting the agglomeration of Fe2O3 grains during calcination. Two-dimensional GO sheets intersect between Fe2O3 nanoparticles, filling microporous defects in the inorganic layer and eliminating pinhole penetration channels in traditional Fe2O3 coatings, significantly improving physical shielding performance. In addition, GO can simultaneously connect the inorganic flake substrate and Fe2O3 grains, enhancing interlayer bonding and providing a smoother, more active composite substrate for subsequent polyaniline coating. Next, polyaniline was in situ coated on the surface of the composite intermediate to obtain a glass flake-graphene oxide composite filler. During this process, under the action of hydrochloric acid, some Fe2O3 dissolved to generate a certain amount of Fe3+. Fe3+ can act as an oxidant to promote the polymerization of aniline (Ding Hangjun, Zhu Changjin, Zhou Zhiming, et al. Ferric chloride oxidized doped polyaniline nanofiber clusters [J]. Acta Polymerica Sinica, 2007(5):462-466.), and assist ammonium persulfate catalysis, thereby improving the coating efficiency of polyaniline.

[0019] Polyaniline and glass flakes have the disadvantages of weak interfacial bonding and easy detachment. In this invention, by depositing Fe2O3-GO hybrid on the glass flakes, the hydroxyl groups of the glass flakes and the molecular chains of polyaniline can be connected simultaneously by chemical bonds, so as to achieve a strong interfacial bond between the inorganic substrate, the inorganic functional layer and the organic anticorrosive layer, thereby significantly improving the bonding strength between polyaniline and glass flakes.

[0020] The beneficial effects of this invention are: In the stainless steel pipe body of the present invention, through the synergistic combination of various elements, the stainless steel pipe body has both excellent mechanical strength and good corrosion resistance. This invention utilizes a coating system made of waterborne polyurethane resin as the main resin and compounded with glass flake-graphene oxide composite filler to form an anti-corrosion coating on the surface of stainless steel pipes. This further enhances the anti-corrosion barrier, heat resistance, and weather resistance, achieving excellent protection for the stainless steel pipe body. Polyurethane resin, in particular, possesses advantages such as good environmental friendliness, strong adhesion, and excellent corrosion and wear resistance.

[0021] The glass flake-graphene oxide composite filler of the present invention forms a composite system by constructing glass flakes, Fe2O3, graphene oxide and polyaniline, which can improve the anti-corrosion performance of the coating through multiple synergistic effects: (1) The sheet-like structure of glass flakes forms a physical barrier that can block most water vapor, salt spray and acid and alkali media from penetrating; the Fe2O3 nanoparticles in the middle nano-interwoven hybrid layer can fill the micropores between the flakes and block the media penetration channels; the GO two-dimensional sheet structure in the middle nano-interwoven hybrid layer can build an ultra-dense barrier network, which greatly extends the penetration path of corrosive media; the outer polyaniline dense film completes the final sealing of the pores. The three-layer structure provides layer-by-layer barrier and builds an all-round physical shielding structure, reducing the probability of contact between corrosive media and stainless steel substrate from the source.

[0022] (2) Doped polyaniline can construct a stable conductive path in the stainless steel coating system, keeping the stainless steel substrate in the passivation potential range and continuously inhibiting the anodic dissolution of the substrate. At the same time, Fe2O3 and polyaniline form a synergistic redox system. When corrosion microcells appear in the system, the composite filler can preferentially participate in the electrode reaction, sacrificing itself to protect the stainless steel substrate and avoid electrochemical corrosion. In addition, the amino and hydroxyl groups on the PANI surface can form a large number of hydrogen bonds with the polyurethane molecular chains of the base resin in the coating, which contain a large number of urethane polar groups, improving the interfacial compatibility between the composite filler and the base resin and achieving uniform dispersion of the composite filler.

[0023] (3) The glass flake-graphene oxide composite filler combines the physical shielding of glass flakes, the passivation and reinforcement of ferric oxide, the barrier enhancement of graphene oxide, and the electrochemical corrosion protection of polyaniline. It can significantly improve the salt spray resistance, acid and alkali resistance, and electrochemical corrosion resistance of stainless steel substrates, while solving the shortcomings of single fillers such as easy agglomeration, poor shielding and short corrosion protection time. Detailed Implementation

[0024] The present invention will be further described in detail below with reference to embodiments, so that those skilled in the art can implement it based on the description.

[0025] It should be understood that terms such as “having,” “comprising,” and “including” as used herein do not exclude the presence or addition of one or more other elements or combinations thereof.

[0026] Unless otherwise specified, the experimental methods used in the following examples are conventional methods. Unless otherwise specified, the materials and reagents used in the following examples are commercially available. For examples where specific conditions are not specified, conventional conditions or conditions recommended by the manufacturer are followed. For reagents or instruments whose manufacturers are not specified, they are all commercially available products.

[0027] In the following examples and comparative examples, the average particle size of the glass flakes was 10 μm, purchased from Hebei Lichen Anticorrosion Coatings Co., Ltd. The waterborne polyurethane resin was HK7080, purchased from Nantong Runfeng Petrochemical Co., Ltd. The curing agent was an isocyanate curing agent, specifically Covestro curing agent Desmodur N 3300.

[0028] Example 1 A corrosion-resistant high-performance stainless steel pipe includes a stainless steel pipe body and an anti-corrosion coating disposed on the surface of the stainless steel pipe body. The raw material components of the stainless steel pipe body include, by mass percentage: C: 0.03%, Cr: 18.6%, Mn: 2.6%, Ni: 9.8%, Mo: 0.74%, Si: 0.42%, N: 0.13%, Nb: 0.09%, balance Fe.

[0029] The manufacturing process of this corrosion-resistant high-performance stainless steel pipe includes the following steps: Step 1: Weigh the raw materials for the stainless steel pipe body according to the above mass percentages, wherein the nitrogen material is introduced through ferrochromium nitride (FeCrN): Step 2: Mix the raw materials of the stainless steel pipe body and put them into an electric arc furnace. Melt at 1580℃ for 15 minutes, with argon blowing for deoxygenation throughout the process. Transfer to an LF refining furnace and refine for 25 minutes. The resulting molten steel is poured into a continuous casting machine to obtain a steel billet. The steel billet is rolled into a steel plate and air-cooled to room temperature. The steel plate is cleaned with anhydrous ethanol to be welded, dried with hot air, and then rolled into a pipe forming machine to obtain the pipe to be welded. The pipe to be welded is then welded using plasma arc welding. Finally, pickling is performed to obtain a pipe blank. The welding width of the pipe to be welded is 4mm. The plasma arc welding conditions are: current 200A, voltage 22V, welding speed 200mm / min, and shielding gas flow rate 30L / min. The tube blank is hot rolled to obtain a rough tube. The rough tube is then solution treated (heated to 1100℃, held for 30 minutes, and then water-quenched to room temperature). After that, it is heated to 1000℃ and then processed by drawing with a fixed mandrel to obtain the stainless steel tube body. Step 3: After polishing the stainless steel pipe body, immerse it in a degreasing solution for 25 minutes, then rinse with water, and finally add it to an acid pickling and passivation solution. Passivate at room temperature for 20 minutes, then rinse with pure water and dry to obtain the pretreated stainless steel pipe body. Apply an anti-corrosion coating to the inner and outer surfaces of the pretreated stainless steel pipe body at a rate of 200 g / m². 2 After spraying, the coating is cured at 85°C for 2 hours to form an anti-corrosion coating, resulting in a high-performance anti-corrosion stainless steel pipe.

[0030] The components of the oil-free liquid are: 500L water, 10kg sodium hydroxide, 30kg sodium phosphate, 4kg sodium gluconate, and 0.8kg fatty alcohol polyoxyethylene ether (AEO-7). The passivation solution consists of 15 wt% nitric acid, 8 wt% hydrofluoric acid, and 0.1 wt% corrosion inhibitor Lan-826.

[0031] In this example, the anti-corrosion coating comprises the following components by weight: The mixture contains 100 parts of waterborne polyurethane resin, 18 parts of glass flake-graphene oxide composite filler, 46 parts of curing agent, 1 part of dispersant, 0.75 parts of defoamer, 0.5 parts of thickener, 1 part of leveling agent, 2.5 parts of film-forming aid, and 35 parts of deionized water.

[0032] The dispersant is BYK-190, the defoamer is BYK-024, the thickener is RM-2020, the leveling agent is BYK-348, and the film-forming aid is propylene glycol methyl ether acetate.

[0033] The glass flake-graphene oxide composite filler was prepared by the following method: S1. Preparation of activated glass flakes: 10g of glass flakes were added to 400mL of deionized water, the pH was adjusted to 4-5 with hydrochloric acid, and the mixture was ultrasonically dispersed for 1h. Then, 1g of silane coupling agent KH-550 and 0.5g of silane coupling agent KH-560 were added, and the mixture was stirred at 65℃ for 3h. After centrifugation and filtration, the solid was washed with ethanol and dried at 90℃ for 6h to obtain activated glass flakes. S2. Deposition of Fe2O3-GO hybrid on activated glass flakes: S2-1. Take 10g of activated glass flakes and add them to 200mL of deionized water. Disperse by ultrasonication for 40min to obtain a glass flake suspension. Take 5.4g of FeCl3·6H2O and add it to 40mL of deionized water. Adjust the pH to 2 with 1mol / L hydrochloric acid and stir for 10min to obtain a ferric chloride solution. Take 0.4g of graphene oxide powder and add it to 60mL of deionized water. Disperse by ultrasonication for 1h to obtain a GO dispersion. S2-2. While stirring, ferric chloride solution and GO dispersion are simultaneously added dropwise to glass flake suspension over a period of 30 min. After the addition is complete, stir for 1 h. Then, adjust the pH to 9 with 0.1 mol / L NaOH solution and stir for 2 h. S2-3. After the reaction is complete, age for 4 hours, filter, wash the solid with deionized water, dry at 100℃ for 4 hours, then calcine at 500℃ for 2 hours, cool to room temperature, grind, and obtain the complex intermediate. S3. Coating the surface of the composite intermediate with polyaniline: 5g of the complex intermediate and 0.3g of sodium dodecylbenzenesulfonate were added to 200mL of deionized water and ultrasonically dispersed for 30min. Then, 16g of aniline was added and stirred for 20min. At the same time, 25mL of 0.2mol / L hydrochloric acid solution and 30mL of ammonium persulfate aqueous solution containing 20g of ammonium persulfate were added dropwise. The mixture was stirred and reacted at 5℃ for 24h. After centrifugation and filtration, the solid was washed with deionized water, vacuum dried at 70℃ for 12h, and ground to obtain the glass flake-graphene oxide composite filler.

[0034] Example 2 A corrosion-resistant high-performance stainless steel pipe includes a stainless steel pipe body and an anti-corrosion coating disposed on the surface of the stainless steel pipe body. The raw material components of the stainless steel pipe body include, by mass percentage: C: 0.03%, Cr: 19.2%, Mn: 2.2%, Ni: 9.0%, Mo: 0.74%, Si: 0.42%, N: 0.13%, Nb: 0.09%, balance Fe.

[0035] The manufacturing process of this corrosion-resistant high-performance stainless steel pipe includes the following steps: Step 1: Weigh the raw materials for the stainless steel pipe body according to the above mass percentages: Step 2: Mix the raw materials of the stainless steel pipe body and put them into an electric arc furnace. Melt at 1550℃ for 18 minutes, with argon blowing for deoxygenation throughout the process. Transfer to an LF refining furnace and refine for 25 minutes. The resulting molten steel is poured into a continuous casting machine to obtain a steel billet. The steel billet is rolled into a steel plate and air-cooled to room temperature. The steel plate is cleaned with anhydrous ethanol to be welded, dried with hot air, and then rolled into a pipe forming machine to obtain the pipe to be welded. The pipe to be welded is then welded using plasma arc welding. Finally, pickling is performed to obtain a pipe blank. The welding width of the pipe to be welded is 4mm. The plasma arc welding conditions are: current 200A, voltage 22V, welding speed 200mm / min, and shielding gas flow rate 30L / min. The tube blank is hot rolled to obtain a rough tube. The rough tube is then solution treated (heated to 11100℃, held for 30 minutes, and then water-quenched to room temperature). After that, it is heated to 1000℃ and then processed by drawing with a fixed mandrel to obtain the stainless steel tube body. Step 3: After polishing the stainless steel pipe body, immerse it in a degreasing solution for 25 minutes, then rinse with water, and finally add it to an acid pickling and passivation solution. Passivate at room temperature for 20 minutes, then rinse with pure water and dry to obtain the pretreated stainless steel pipe body. Apply an anti-corrosion coating to the inner and outer surfaces of the pretreated stainless steel pipe body at a rate of 200 g / m². 2 After spraying, the coating is cured at 85°C for 2 hours to form an anti-corrosion coating, resulting in a high-performance anti-corrosion stainless steel pipe.

[0036] The components of the oil-free liquid are: 500L water, 10kg sodium hydroxide, 30kg sodium phosphate, 4kg sodium gluconate, and 0.8kg fatty alcohol polyoxyethylene ether (AEO-7). The passivation solution consists of 15 wt% nitric acid, 8 wt% hydrofluoric acid, and 0.1 wt% corrosion inhibitor Lan-826.

[0037] The anti-corrosion coating in this example comprises the following components by weight: The mixture contains 100 parts of waterborne polyurethane resin, 16 parts of glass flake-graphene oxide composite filler, 46 parts of curing agent, 0.8 parts of dispersant, 0.75 parts of defoamer, 0.6 parts of thickener, 1 part of leveling agent, 2.5 parts of film-forming aid, and 35 parts of deionized water.

[0038] The dispersant is BYK-190, the defoamer is BYK-024, the thickener is RM-2020, the leveling agent is BYK-348, and the film-forming aid is propylene glycol methyl ether acetate.

[0039] The glass flake-graphene oxide composite filler used is the same as in Example 1.

[0040] Example 3 A corrosion-resistant high-performance stainless steel pipe includes a stainless steel pipe body and an anti-corrosion coating disposed on the surface of the stainless steel pipe body. The raw material components of the stainless steel pipe body include, by mass percentage: C: 0.03%, Cr: 17.5%, Mn: 3.3%, Ni: 10.5%, Mo: 0.74%, Si: 0.42%, N: 0.13%, Nb: 0.09%, balance Fe.

[0041] The manufacturing process of this corrosion-resistant high-performance stainless steel pipe includes the following steps: Step 1: Weigh the raw materials for the stainless steel pipe body according to the above mass percentages: Step 2: Mix the raw materials of the stainless steel pipe body and put them into an electric arc furnace. Melt at 1600℃ for 12 minutes, with argon blowing for deoxygenation throughout the process. Transfer to an LF refining furnace and refine for 25 minutes. The resulting molten steel is poured into a continuous casting machine to obtain a steel billet. The steel billet is rolled into a steel plate and air-cooled to room temperature. The steel plate is cleaned with anhydrous ethanol to be welded, dried with hot air, and then rolled into a pipe forming machine to obtain the pipe to be welded. The pipe to be welded is then welded using plasma arc welding. Finally, pickling is performed to obtain a pipe blank. The welding width of the pipe to be welded is 4mm. The plasma arc welding conditions are: current 200A, voltage 22V, welding speed 200mm / min, and shielding gas flow rate 30L / min. The tube blank is hot rolled to obtain a rough tube. The rough tube is then solution treated (heated to 1000℃, held for 40 minutes, and then water-cooled and quenched to room temperature). After that, it is heated to 1000℃ and then processed by drawing with a fixed mandrel to obtain the stainless steel tube body. Step 3: After polishing the stainless steel pipe body, immerse it in a degreasing solution for 25 minutes, then rinse with water, and finally add it to an acid pickling and passivation solution. Passivate at room temperature for 20 minutes, then rinse with pure water and dry to obtain the pretreated stainless steel pipe body. Apply an anti-corrosion coating to the inner and outer surfaces of the pretreated stainless steel pipe body at a rate of 200 g / m². 2 After spraying, the coating is cured at 85°C for 2 hours to form an anti-corrosion coating, resulting in a high-performance anti-corrosion stainless steel pipe.

[0042] The components of the oil-free liquid are: 500L water, 10kg sodium hydroxide, 30kg sodium phosphate, 4kg sodium gluconate, and 0.8kg fatty alcohol polyoxyethylene ether (AEO-7). The passivation solution consists of 15 wt% nitric acid, 8 wt% hydrofluoric acid, and 0.1 wt% corrosion inhibitor Lan-826.

[0043] In this example, the anti-corrosion coating comprises the following components by weight: The mixture contains 100 parts of waterborne polyurethane resin, 20 parts of glass flake-graphene oxide composite filler, 46 parts of curing agent, 1.5 parts of dispersant, 0.75 parts of defoamer, 0.35 parts of thickener, 1 part of leveling agent, 2.5 parts of film-forming aid, and 35 parts of deionized water.

[0044] The dispersant is BYK-190, the defoamer is BYK-024, the thickener is RM-2020, the leveling agent is BYK-348, and the film-forming aid is propylene glycol methyl ether acetate.

[0045] The glass flake-graphene oxide composite filler used is the same as in Example 1.

[0046] Example 4 A corrosion-resistant high-performance stainless steel pipe includes a stainless steel pipe body and an anti-corrosion coating disposed on the surface of the stainless steel pipe body. The raw material components of the stainless steel pipe body include, by mass percentage: C: 0.035%, Cr: 18.2%, Mn: 2.9%, Ni: 9.5%, Mo: 0.81%, Si: 0.42%, N: 0.15%, Nb: 0.08%, balance Fe.

[0047] The manufacturing process of this corrosion-resistant high-performance stainless steel pipe includes the following steps: Step 1: Weigh the raw materials for the stainless steel pipe body according to the above mass percentages: Step 2: Mix the raw materials of the stainless steel pipe body and put them into an electric arc furnace. Melt at 1580℃ for 15 minutes, with argon blowing for deoxygenation throughout the process. Transfer to an LF refining furnace and refine for 25 minutes. The resulting molten steel is poured into a continuous casting machine to obtain a steel billet. The steel billet is rolled into a steel plate and air-cooled to room temperature. The steel plate is cleaned with anhydrous ethanol to be welded, dried with hot air, and then rolled into a pipe forming machine to obtain the pipe to be welded. The pipe to be welded is then welded using plasma arc welding. Finally, pickling is performed to obtain a pipe blank. The welding width of the pipe to be welded is 4mm. The plasma arc welding conditions are: current 200A, voltage 22V, welding speed 200mm / min, and shielding gas flow rate 30L / min. The tube blank is hot rolled to obtain a rough tube. The rough tube is then solution treated (heated to 1100℃, held for 30 minutes, and then water-quenched to room temperature). After that, it is heated to 1000℃ and then processed by drawing with a fixed mandrel to obtain the stainless steel tube body. Step 3: After polishing the stainless steel pipe body, immerse it in a degreasing solution for 25 minutes, then rinse with water, and finally add it to an acid pickling and passivation solution. Passivate at room temperature for 20 minutes, then rinse with pure water and dry to obtain the pretreated stainless steel pipe body. Apply an anti-corrosion coating to the inner and outer surfaces of the pretreated stainless steel pipe body at a rate of 200 g / m². 2 After spraying, the coating is cured at 85°C for 2 hours to form an anti-corrosion coating, resulting in a high-performance anti-corrosion stainless steel pipe.

[0048] The components of the oil-free liquid are: 500L water, 10kg sodium hydroxide, 30kg sodium phosphate, 4kg sodium gluconate, and 0.8kg fatty alcohol polyoxyethylene ether (AEO-7). The passivation solution consists of 15 wt% nitric acid, 8 wt% hydrofluoric acid, and 0.1 wt% corrosion inhibitor Lan-826.

[0049] In this example, the anti-corrosion coating is the same as in Example 1.

[0050] Comparative Example 1 The only difference between this example and Example 1 is that: In this example, the anti-corrosion coating comprises the following components by weight: The mixture contains 100 parts of waterborne polyurethane resin, 4 parts of activated glass flakes, 1 part of dispersant, 46 parts of curing agent, 0.75 parts of defoamer, 0.5 parts of thickener, 1 part of leveling agent, 2.5 parts of film-forming aid, and 35 parts of deionized water.

[0051] The dispersant is BYK-190, the defoamer is BYK-024, the thickener is RM-2020, the leveling agent is BYK-348, and the film-forming aid is propylene glycol methyl ether acetate.

[0052] The preparation method of the activated glass flakes is the same as in Example 1.

[0053] Comparative Example 2 The only difference between this example and Example 1 is that: In this example, a modified glass flake filler is used instead of the glass flake-graphene oxide composite filler in Example 1. The modified glass flake filler is prepared by the following method: S1. Prepare activated glass flakes, the specific steps are the same as in Example 1; S2, S3: Coating the surface of activated glass flakes with polyaniline: 5g of activated glass flakes and 0.3g of sodium dodecylbenzenesulfonate were added to 200mL of deionized water and ultrasonically dispersed for 30min. Then, 16g of aniline was added and stirred for 20min. Simultaneously, 25mL of 0.2mol / L hydrochloric acid solution and 30mL of ammonium persulfate aqueous solution containing 20g of ammonium persulfate were added dropwise. The mixture was stirred and reacted at 5℃ for 24h. After centrifugation and filtration, the solid was washed with deionized water, vacuum dried at 70℃ for 12h, and ground to obtain the modified glass flake filler.

[0054] Comparative Example 3 The only difference between this example and Example 1 is that: In this example, a modified glass flake filler is used instead of the glass flake-graphene oxide composite filler in Example 1. The modified glass flake filler is prepared by the following method: S1. Prepare activated glass flakes, the specific steps are the same as in Example 1; S2. Deposition of Fe2O3 on activated glass flakes: S2-1. Take 10g of activated glass flakes and add them to 200mL of deionized water. Disperse them by sonication for 40min to obtain a glass flake suspension. Take 5.4g of FeCl3·6H2O and add it to 40mL of deionized water. Adjust the pH to 2 with 1mol / L hydrochloric acid and stir for 10min to obtain a ferric chloride solution. S2-2. Add ferric chloride solution dropwise to the glass flake suspension with stirring over a period of 30 minutes. After the addition is complete, stir for 1 hour. Then, adjust the pH to 9 with 0.1 mol / L NaOH solution and stir for 2 hours. S2-3. After the reaction is complete, age for 4 hours, filter, wash the solid with deionized water, dry at 100℃ for 4 hours, then calcine at 500℃ for 2 hours, cool to room temperature, grind, and obtain the complex intermediate. S3. Coating the surface of the composite intermediate with polyaniline: 5g of the complex intermediate and 0.3g of sodium dodecylbenzenesulfonate were added to 200mL of deionized water and ultrasonically dispersed for 30min. Then, 16g of aniline was added and stirred for 20min. At the same time, 25mL of 0.2mol / L hydrochloric acid solution and 30mL of ammonium persulfate aqueous solution containing 20g of ammonium persulfate were added dropwise. The mixture was stirred and reacted at 5℃ for 24h. After centrifugation and filtration, the solid was washed with deionized water, vacuum dried at 70℃ for 12h, and ground to obtain the modified glass flake filler.

[0055] Comparative Example 4 The only difference between this example and Example 1 is that: In this example, the anti-corrosion coating comprises the following components by weight: The composition includes 100 parts waterborne polyurethane resin, 5 parts composite filler, 46 parts curing agent, 1 part dispersant, 0.75 parts defoamer, 0.5 parts thickener, 1 part leveling agent, 2.5 parts film-forming aid, and 35 parts deionized water.

[0056] The dispersant is BYK-190, the defoamer is BYK-024, the thickener is RM-2020, the leveling agent is BYK-348, and the film-forming aid is propylene glycol methyl ether acetate.

[0057] The composite filler is the composite intermediate prepared in Example 1.

[0058] Performance testing 1. Tensile strength Tested in accordance with standard GB / T 228.1-2021 "Metallic materials, tensile testing - Part 1: Test method at room temperature".

[0059] 2. Corrosion resistance Samples were prepared using the methods described in the examples. The sample dimensions were 200 mm × 100 mm × 5 mm, and all surfaces of the sample were coated with an anti-corrosion coating. The samples were subjected to a neutral salt spray test according to the standard GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test", with a temperature of 35℃, a sodium chloride solution concentration of 50 g / L, a pH of 7.0, and a test duration of 180 h. The weight loss of the test sample after the test was measured.

[0060] The test results are shown in Table 1 below: Table 1 Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Tensile strength / MPa 636 627 631 624 632 638 631 636 Loss of mass / g 0.17 0.21 0.15 0.22 1.05 0.61 0.32 0.79 As can be seen from the test results in Table 1, the corrosion-resistant high-performance stainless steel pipes prepared in Examples 1-4 possess both excellent mechanical strength and corrosion resistance. In Comparative Example 1, activated glass flakes were used as fillers, resulting in a significant decrease in corrosion resistance. The results of Comparative Example 2 indicate that depositing Fe2O3-GO hybrids on activated glass flakes can significantly improve the corrosion resistance of the coating. The results of Comparative Example 3 indicate that GO can improve corrosion resistance. The corrosion resistance of Comparative Example 4 decreased significantly, partly due to the lack of polyaniline coating, which severely reduced the dispersion performance of the filler, and partly due to the absence of the electrochemical corrosion protection provided by polyaniline.

[0061] Although the embodiments of the present invention have been disclosed above, they are not limited to the applications listed in the specification and embodiments. They can be applied to various fields suitable for the present invention. For those skilled in the art, other modifications can be easily made. Therefore, without departing from the general concept defined by the claims and their equivalents, the present invention is not limited to the specific details.

Claims

1. A corrosion-resistant, high-performance stainless steel pipe, characterized in that, The stainless steel pipe body includes a stainless steel pipe body and an anti-corrosion coating disposed on the surface of the stainless steel pipe body. The raw material components of the stainless steel pipe body include, by mass percentage: C: 0.025-0.036%, Cr: 17.5-20.8%, Mn: 1.4-2.2%, Ni: 8.0-11.5%, Mo: 0.46-0.92%, Si: 0.35-0.52%, N: 0.10-0.16%, Nb: 0.06-0.11%, balance Fe.

2. The corrosion-resistant high-performance stainless steel pipe according to claim 1, characterized in that, The anti-corrosion coating is obtained by applying an anti-corrosion paint and then curing it. The anti-corrosion paint comprises the following components by weight: The ingredients are: 100 parts waterborne polyurethane resin, 15-25 parts glass flake-graphene oxide composite filler, 34-55 parts curing agent, 0.4-1.6 parts dispersant, 0.5-2 parts defoamer, 0.2-0.8 parts thickener, 0.5-2 parts leveling agent, 1-4 parts film-forming aid, and 20-40 parts deionized water.

3. The corrosion-resistant high-performance stainless steel pipe according to claim 2, characterized in that, The glass flake-graphene oxide composite filler was prepared by the following method: S1. Modify the glass flakes with a silane coupling agent to obtain activated glass flakes: S2. Fe2O3-GO hybrid is deposited on activated glass flakes to obtain the complex intermediate; S3. Coating the surface of the composite intermediate with polyaniline to obtain the glass flake-graphene oxide composite filler.

4. The corrosion-resistant high-performance stainless steel pipe according to claim 3, characterized in that, The silane coupling agent used in step S1 is a mixture of KH-550 and KH-560 in a mass ratio of 1:0.2~0.

8.

5. The corrosion-resistant high-performance stainless steel pipe according to claim 4, characterized in that, Step S1 is as follows: glass flakes are added to deionized water, the pH is adjusted to 4-5 with hydrochloric acid, and after ultrasonic dispersion, silane coupling agents KH-550 and KH-560 are added. The mixture is heated and stirred to react. After the reaction is completed, the mixture is filtered, and the solid is washed and dried to obtain activated glass flakes.

6. The corrosion-resistant high-performance stainless steel pipe according to claim 3, characterized in that, Step S2 is as follows: S2-1. Take activated glass flakes and disperse them in deionized water to obtain a glass flake suspension; take FeCl3·6H2O and add it to 40mL of deionized water, adjust the pH to 1-2, and obtain a ferric chloride solution; take graphene oxide powder and disperse it in deionized water to obtain a GO dispersion. S2-2. While stirring, ferric chloride solution and GO dispersion are simultaneously added dropwise to the glass flake suspension. Stir, adjust the pH to 8.5-10, and stir to react. S2-3. After the reaction is complete, the mixture is aged, filtered, washed, dried, calcined, cooled, and ground to obtain the complex intermediate.

7. The corrosion-resistant high-performance stainless steel pipe according to claim 3, characterized in that, Step S3 specifically involves adding the composite intermediate and sodium dodecylbenzenesulfonate to deionized water, dispersing it ultrasonically, adding aniline, stirring, and simultaneously adding hydrochloric acid solution and ammonium persulfate aqueous solution. After the reaction is complete, the mixture is filtered, and the solid is washed, dried, and ground to obtain the glass flake-graphene oxide composite filler.

8. The corrosion-resistant high-performance stainless steel pipe according to claim 3, characterized in that, The glass flake-graphene oxide composite filler was prepared by the following method: S1. Preparation of activated glass flakes: Add 5-20g of glass flakes to 200-800mL of deionized water, adjust the pH to 4-5 with hydrochloric acid, and sonicate for 0.5-2h. Then add 0.5-2g of silane coupling agent KH-550 and 0.25-1g of silane coupling agent KH-560, stir and react at 50-75℃ for 1.5-6h, centrifuge and filter, wash the solid with ethanol, and dry to obtain activated glass flakes. S2. Deposition of Fe2O3-GO hybrid on activated glass flakes: S2-1. Take 5-20g of activated glass flakes and add them to 100-400mL of deionized water. Disperse by ultrasonication for 20-80min to obtain a glass flake suspension. Take 2.7-10.8g of FeCl3·6H2O and add it to 20-80mL of deionized water. Adjust the pH to 2 with hydrochloric acid and stir for 5-20min to obtain a ferric chloride solution. Take 0.2-0.8g of graphene oxide powder and add it to 30-120mL of deionized water. Disperse by ultrasonication for 0.5-2h to obtain a GO dispersion. S2-2. While stirring, ferric chloride solution and GO dispersion are simultaneously added dropwise to the glass flake suspension over a period of 15-60 min. After the addition is complete, stir for 0.5-2 h. Then, adjust the pH to 8.5-10 with 0.05-0.2 mol / L NaOH solution and stir the reaction for 1-4 h. S2-3. After the reaction is complete, age for 2-8 hours, filter, wash the solid with deionized water, dry at 90-110℃ for 2-8 hours, then calcine at 450-550℃ for 1.5-4 hours, cool to room temperature, grind, and obtain the complex intermediate. S3. Coating the surface of the complex intermediate with polyaniline: Add 2.5-10g of the complex intermediate and 0.15-0.6g of sodium dodecylbenzenesulfonate to 100-400mL of deionized water and sonicate for 15-60min. Then add 8-32g of aniline and stir for 10-40min. Simultaneously add 10-50mL of 0.1-0.5mol / L hydrochloric acid solution and 10-50mL of ammonium persulfate aqueous solution containing 10-30g of ammonium persulfate. Stir and react at 0-10℃ for 12-48h. Centrifuge and filter. Wash the solid with deionized water, vacuum dry, and grind to obtain the glass flake-graphene oxide composite filler.

9. The corrosion-resistant high-performance stainless steel pipe according to claim 2, characterized in that, The dispersant is BYK-190, the defoamer is BYK-024, the thickener is RM-2020, the leveling agent is BYK-348, and the film-forming aid is propylene glycol methyl ether acetate.

10. A manufacturing process for a corrosion-resistant high-performance stainless steel pipe as described in any one of claims 1-9, characterized in that, Includes the following steps: Step 1: Weigh the raw materials for the stainless steel pipe body according to the following mass percentages: C: 0.025-0.036%, Cr: 17.5-20.8%, Mn: 1.4-2.2%, Ni: 8.0-11.5%, Mo: 0.46-0.92%, Si: 0.35-0.52%, N: 0.10-0.16%, Nb: 0.06-0.11%, balance Fe; Step 2: Mix and melt the raw materials of the stainless steel pipe body, cast the molten steel to obtain a steel plate, and then roll, weld, hot roll, and solution treat the steel plate to obtain the stainless steel pipe body. Step 3: Spray anti-corrosion coating on the inner and outer surfaces of the stainless steel pipe body, dry and cure to form an anti-corrosion coating, and obtain the anti-corrosion high-performance stainless steel pipe.

Citation Information

Patent Citations

  • A corrosion protection process for stainless steel pipe fittings

    CN113430509B